2015
DOI: 10.1007/s00737-015-0551-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-infant mental health: postpartum group intervention

Abstract: Dyadic interactions associated with maternal depression and anxiety may perpetuate maternal mental illness and impact infant attachment. Individual and maternal-dyadic therapies are effective but resource intensive. We assessed feasibility, acceptability, and preliminary efficacy of a newly developed maternal-infant dyadic group therapy intervention. This was an open-label pilot study targeting mothers with mood or anxiety disorders, and their infants aged 6 to 12 months. We conducted three 12-week groups comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
2
27
0
5
Order By: Relevance
“…In addition, evidence indicates that the coexistence of stress, anxiety, and depressive symptoms occur during the postpartum period [17]. Timely and efficacious intervention is important during the postpartum period, especially when considering the adverse short- and long-term maternal health outcomes and child development outcomes [22-24]. Strong evidence supports that CBT is effective for treatment and prevention during the postpartum period [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence indicates that the coexistence of stress, anxiety, and depressive symptoms occur during the postpartum period [17]. Timely and efficacious intervention is important during the postpartum period, especially when considering the adverse short- and long-term maternal health outcomes and child development outcomes [22-24]. Strong evidence supports that CBT is effective for treatment and prevention during the postpartum period [25].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have assessed the efficacy and cost differential of postpartum groups as compared to home visits. The studies suggest that groups can improve parenting knowledge (McNeil & Holland, 1972) and maternal mental health (de Camps Meschino, Philipp, Israel, & Vigod, 2016) at a lower cost. However, these studies did not measure the impact upon child abuse events, and neither study was an RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a pilot randomized clinical trial of a mindfulness program for breastfeeding mothers suggested benefits of increased self‐efficacy, improved mood, and increased self‐compassion . A small pilot study of an intervention that included a mindfulness component for mothers with mood or anxiety disorders who had 6‐ to 12‐month‐old infants showed significant reduction in depression scores (t = 3.31, P = .008) …”
Section: Discussionmentioning
confidence: 99%
“…29 A small pilot study of an intervention that included a mindfulness component for mothers with mood or anxiety disorders who had 6-to 12-month-old infants showed significant reduction in depression scores (t = 3.31, P = .008). 30 Four of the participants described significant medical complications that affected their pregnancy, birth, or postpartum recovery. Unlike other approaches to childbirth education, MBCP does not promise a particular childbirth experience or outcome.…”
Section: Discussionmentioning
confidence: 99%